2014
DOI: 10.1007/s10126-014-9579-7
|View full text |Cite
|
Sign up to set email alerts
|

Divergence in Expression of Candidate Genes for the Smoltification Process Between Juvenile Resident Rainbow and Anadromous Steelhead Trout

Abstract: Rainbow and steelhead trout (Oncorhynchus mykiss), among other salmonid fishes, exhibit tremendous life history diversity, foremost of which is variation in migratory propensity. While some individuals possess the ability to undertake an anadromous marine migration, others remain resident in freshwater throughout their life cycle. Those that will migrate undergo tremendous physiological, morphological, and behavioral transformations in a process called smoltification which transitions freshwater-adapted parr t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 90 publications
1
15
0
Order By: Relevance
“…Although it is difficult to know whether the genetic correlations and overlapping QTL represent the pleiotropic effect or close linkage of genes ( Flint and Mackay 2009 ; Stearns 2010 ), the close genetic relationship between many of these traits and the distribution of QTL suggest evolutionary forces acting on a single trait will be constrained, or correlated phenotypic responses to selection would be anticipated. Furthermore, analysis in this extended population provides additional support for the potential pleiotropic nature of QTL on Omy12 and Omy14 found in Hecht et al (2012) , and that these regions deserve further inquiry to identify potential candidate genes of the migratory life history within this population ( Hecht et al 2014 ).…”
Section: Discussionmentioning
confidence: 67%
“…Although it is difficult to know whether the genetic correlations and overlapping QTL represent the pleiotropic effect or close linkage of genes ( Flint and Mackay 2009 ; Stearns 2010 ), the close genetic relationship between many of these traits and the distribution of QTL suggest evolutionary forces acting on a single trait will be constrained, or correlated phenotypic responses to selection would be anticipated. Furthermore, analysis in this extended population provides additional support for the potential pleiotropic nature of QTL on Omy12 and Omy14 found in Hecht et al (2012) , and that these regions deserve further inquiry to identify potential candidate genes of the migratory life history within this population ( Hecht et al 2014 ).…”
Section: Discussionmentioning
confidence: 67%
“…; Hecht et al . ). However, as stated, these studies sampled individuals that had already undergone smoltification.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, it is rare for these types of studies to detect the causal gene influencing traits of interest. Finally, expression-based approaches such as qPCR (Amstutz et al 2006;Aykanat et al 2011;Hecht et al 2014), microarray analysis (Giger et al 2008;Nolte et al 2009;Robertson & McCormick 2012;Sutherland et al 2014) and gene network analysis (Filteau et al 2013) have demonstrated differential gene expression between fish with different life histories. Combining approaches of gene expression and mapping provides an efficient means to identify candidate genes involved in life history by identifying differentially expressed genes in genomic regions previously associated with life history variation (Liu et al 2001;Cox et al 2002;Wayne & McIntyre 2002;Tabakoff et al 2003;Xu et al 2011;Poelstra et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the last two decades, and especially after the publication of the Atlantic salmon (Salmo salar) and rainbow trout (Oncorhynchus mykiss) genomes [18,19], an increasing number of DNA and RNA-based studies have been published on smoltification. Findings include gene expression changes after seawater transfer [20][21][22], epigenetic modifications [23], quantitative trait loci [24], and gene expression patterns [25][26][27] associated with the likelihood of steelhead trout to migrate to seawater. At the protein level, studies are restricted to targeted, top-down studies of key protein hormones such as insulin, insulin-like growth factor 1 (IGF-I), growth hormone (GH) and their receptors [8,28,29].…”
Section: Introductionmentioning
confidence: 99%